"Everybody Thinks Public Libraries Have Only Books": Public Library Usage and Settlement of Bangladeshi Immigrants in Canada. Issue 3 (4th May 2023) - Shuva, Nafiz Zaman
ABSTRACT: Many public libraries in Canada offer services and programs for immigrants, including employment assistance to assist newcomers with their settlement in Canada. Using a mixed method research design, this study explores the use of public libraries by Bangladeshi immigrants in Canada including their use of public library settlement services, along with their pre-migration access to public library services. The study finds immigrants' use of public libraries declines over time. However, it is also evident in this study that public libraries played a positive role in newcomers' settlement into Canadian society. The findings related to the lack of familiarity with public libraries in a pre-arrival context highlight the importance of having a strong public library outreach program for immigrant populations. The author urges public libraries offering services to immigrants to make meaningful partnerships with pre-and post-arrival settlement agencies, local ethnic community and religious organizations, and ethnic media to spread the word about public library programs and services for immigrants.